Outcome case study of no-burning management solutions for rice crop residues - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Using the CCAFS & WHEAT science evidence, Govt of India launched a new scheme to eliminate residue burning in India. The outcome case was reported in 2017 report and also CGIAR system level report as a case study. However, the adoption of happy seeder (no-till) wheat without burning rice residue has been increased significantly covering 0.8 million ha in north-west India